Personal training in Europe : the most comprehensive international study on personal training - Gronau, Niels, ....-; Titze, Gregor, ....- (Den Bosch : Black Box Publishers, 2018)
Personal Training is an exciting and growing niche of the overall fitness market with a high level of popularity and penetration in markets like the United States or the United Kingdom. But also in other countries more and more Personal Trainers seem to be present. And fitness club operators from the budget to the high-end segment integrate this particularly personal offering into their portfolio of services. Despite this growing interest the existing research and available information on Personal Training has been very limited. Now, this book Personal Training in Europe comprises the results of a comprehensive research project conducted in 15 European countries. The results are based on the participation of more than 3,000 Personal Trainers. The study is the first of its kind covering a wide range of relevant topics including basic market numbers, detailed characteristics of Personal Trainers and their offering as well as information on clients of this specific offering. This book is written for fitness professionals already being or planning to be active as Personal Trainers and club owners or managers who want to learn more about the Personal Training segment in their individual country.
Keywords: Krachttraining